Evaluation of bio-formulation from Chaetomium elatum ChE01 to control banana anthracnose caused by Colletotrichum musae - Soytong, K.; Suthammarit, S.; Kanokmedhakul, S. (International Journal of Agricultural Technology, 2019)
Anthracnose of banana is proved to cause by Colletotrichum musae. Chaetomium elatum ChE01 inhibited the growth of C. musae within 30 days in bi-culture plates over 60 % and inhibited the spore production of C. musae of 57 %. The metabolites from C. elatum ChE01 actively fungal activity against C. musae for spore inhibition which crude methanol, crude ethyl acetate and crude hexane extracts at the ED50 value was 5.43, 7.43 and 19.62 ppm., respectively. The new bio-formulation of C. elatum ChE01 reduced disease incidence of banana anthracnose of 13.34 % compared to benomyl that reduced the disease incidence of 13.05 %. Moreover, the crude extract mixture of C. elatum ChE01 and spore suspension of C. elatum ChE01 reduced the anthracnose incidence of 2.13 and 2.04 %, respectively. The research finding is reported for the first time that bioformulations of C. elatum ChE01 could control banana anthracnose caused by C. musae.